Personal and regional redistribution through public finance : The case of provincial governments in Argentina - Cont, Walter Alberto (2009)
In a federal system, income distribution is affected by the decision of many public economic agents in at least two dimensions: personal and regional. Through public budgeting, and the interaction of expenditures and taxes, a subnational government typically affects the personal distribution of income, and also the regional distribution of income if the subnational budget is financed with national taxes, through revenue-sharing (coparticipation) regimes -because this regime redistributes tax revenues among provinces. Most research in this field focuses on the impact of public budget on either personal or regional distribution of income. Very few papers integrate both effects. This paper studies the impact of provincial government budgets (which represent around 50% of total public expenditures, and around 60% of funds to finance them comes from revenue-sharing) on the distribution of income in Argentina using budget information for year 2004. This paper reveals the importance of considering the impact of fiscal policy on income distribution at the provincial level, because effects are different by province. The aggregation of provinces hides inter-provincial effects because some province may finance or benefit from the revenue-sharing scheme. Taking this effect into consideration, we find that the progressiveness of subnational expenditures and taxes interact with the revenuesharing regime, reinforcing progressivity in “net-receiving” provinces but creating a trade-off between progressivity and (negative) regional transfer in “net-financing” ones. In the latter provinces, however, the net effect of provincial budget is also progressive.